Diagnostic Value of Neutrophil-to-Lymphocyte, Platelet-to-Lymphocyte and Monocyte-to-Lymphocyte Ratio for COVID-19 Screening - JB. Suparyatmo; Amiroh Kurniati; Johannes Dwight Risamasu (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
COVID-19 is caused by SARS-CoV-2, which can affect all ages. The prevalence of COVID-19 reported by the World Health Organization (WHO) in March 2020 was 3 million cases worldwide. The number of confirmed cases of COVID-19 reported by WHO in June 2020 in Indonesia was 28,233 cases. This research was an observational analytic study with a cross-sectional approach to determine the performance and cut-off of NLR, PLR, and MLR as a screening for COVID-19 infection conducted at the RSDM Clinical Pathology Installation in Surakarta from March 2020 to April 2021. The total subjects of this study were 348 people. The characteristics of the research subjects were presented in descriptive form. The Receiver Operating Characteristic (ROC) curve and the Area Under Curve (AUC) were used to determine the cut-off of NLR, PLR, and MLR. The results were presented in a 2x2 table. A computer program was used for statistical analysis. There was a significant relationship between NLR, PLR, and MLR and the incidence of COVID-19. A cut-off > 3.010, sensitivity 66.5%, specificity 61.9%, PPV 0.773, NPV 0.487, LR (+) 1.744, and LR (-) 0.541 were obtained for NLR as a COVID-19 screening. A cut-off > 157.035, sensitivity 63%, specificity 60.2%, PPV 0.755, NPV 0.455, LR (+) 1.583, and LR (-) 0.614 were obtained for PLR as a COVID-19 screening. A cut-off > 0.296, sensitivity 60%, specificity 58.5%, PPV 0.738, NPV 0.429, LR (+) 1.445, and LR (-) 0.684 were obtained for MLR as a screening for COVID-19. NLR and PLR cannot be used as the main screening biomarkers for COVID-19. Regardless of the clinical manifestations of patients, other biomarkers such as antigen swabs should be considered.